1998
DOI: 10.1002/(sici)1099-1700(1998100)14:4<231::aid-smi802>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling occupational stress and health: the impact of the demand–control model on academic research and on workplace practice

Abstract: Reality catches up with wishful thinking: If highly reactive chelated amino acid ester enolates are used as nucleophiles in palladium‐catalyzed allylic alkylations, the π‐σ‐π isomerization of π‐allyl – palladium intermediates can be suppressed nearly completely. This opens up new synthetic applications, such as stereoselective reactions of (Z)‐allyl carbonates [Eq. (1); Tfa=trifluoracetyl; LHMDS=lithium bis(trimethylsilyl)amide].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…These findings corroborate those of recent reviews of the DC model 44) . Generally, current findings provide consistent empirical support for the view that high strain jobs (high demand, low control) give rise to poor well-being 13,25,36) .…”
Section: Job Strainsupporting
confidence: 91%
“…These findings corroborate those of recent reviews of the DC model 44) . Generally, current findings provide consistent empirical support for the view that high strain jobs (high demand, low control) give rise to poor well-being 13,25,36) .…”
Section: Job Strainsupporting
confidence: 91%
“…However, it is important that the factors are general enough to be applicable in different settings, and that normative values can be used for benchmarking (Faragher, Cooper & Cartwright, 2004). Jones and co-workers (Jones, Bright, Searle & Cooper, 1998) concluded that: "Knowledge of a risk factor can only be useful if it is sufficiently specified to inform us about appropriate prevention actions" (p. 235).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most influential approaches to studying job stress is Karasek's (1979) job strain model, which is one of the few clearly specified and parsimonious theories enabling easy assessment of job stress ( Jones, Bright, Searle, & Cooper, 1998). The model suggests that a combination of high job demands (e.g.…”
Section: Job Strainmentioning
confidence: 99%